THE PLANNING AND CONDUCTING TRANSPORT AND TRANSPORT-SOCIOLOGICAL SURVEYS FOR THE DEVELOPMENT OF A LOCAL PROJECT OF THE BELGOROD URBAN AGGLOMERATION - Kushchenko, Liliya; Kushchenko, Sergey; Novikov, Alexander; Novikov, Ivan (Journal of Applied Engineering Science, 2021)
When forming industrial and economic relations, there is a need for purposeful planning and development of urban agglomerations. The most urgent problem of spatial development of regions is due to the existing differences in the standard of living, conditions, as well as the scheme of the street and road network, namely, peripheral points. An important role in ensuring a high level of development of all the territories of the region is played by "group" forms of highly concentrated settlement, such as urban agglomerations. The development of urban agglomeration makes it possible to distribute industrial production, as well as rationally arrange them in relation to residential development, which will further improve economic and environmental indicators in large cities. In addition, an urban agglomeration that has significantly more opportunities for development is an environment that has properties favorable for inertial processes [6]. The article discusses the features of the formation of the urban agglomeration of the city of Belgorod. The territorial and functional structure of the urban agglomeration is presented. Priorities for the development of the urban agglomeration are outlined. The influence of the agglomeration effect on the economic growth of the region is revealed.